High-speed photonics interconnects - Chrostowski, Lukas; Iniewski, Krzysztof, 1960- (Devices, circuits, and systems., 2013)
Dramatic increases in processing power have rapidly scaled on-chip aggregate bandwidths into the Tb/s range. This necessitates a corresponding increase in the amount of data communicated between chips, so as not to limit overall system performance. To meet the increasing demand for interchip communication bandwidth, researchers are investigating the use of high-speed optical interconnect architectures. Unlike their electrical counterparts, optical interconnects offer high bandwidth and negligible frequency-dependent loss, making possible per-channel data rates of more than 10 Gb/s. High-Speed.